Audiovisual Preservation and Conservation in Ghana Broadcasting Corporation - Edu, Frank Paa Kwesi (UniMAC-GIJ, 2021)
The research investigated audiovisual (AV) preservation and conservation in Ghana Broadcasting Corporation. This phenomenon is challenging and complex but many aspects around storage, care, and access of these collections must be considered before any preservation and conservation methods. The research approached issues surrounding preserving and conserving of AV formats from GBC’s heritage point of view. The objectives of the research were to: what were the storage carrier formats used for preserving and conserving of AVs in the film/video repository; what were the challenges in preserving and conserving of AVs in the film/video repository; and to determine what will be the future possibilities of digitizing AVs. To meet the set objectives and find answers, qualitative analytic method termed content analysis was used in analyzing data with ten (10) members of staff as the target population. As a qualitative research, unstructured interviews and observations methods were used and the data collected analyzed qualitatively, using content analytic techniques stemming from the nature of data collected with thematic subject identification from the field notes. The challenges confronting GBC’s repository were enormous with data evidence pointing to lack of funding, lack of awareness of the relevance, lack of training, management and research opportunities, lack of expertise in preventing deterioration, temperature and humidness. Others challenges discovered were the standards of preserving and conserving, no playback machines, technological obsolescence. Data based analysis established that GBC’s management and board of governance had incubated the idea of digitization but not executed. As of now the repository is experiencing losses through deterioration, obsolescence of equipment playback, as well as other possible means such as handling, playback damage, high temperature and mould infestation amongst others. The research concluded based on the evidence of findings that digitization is an armament. Recommendations made include funding, training of staff, collaboration with professional associations, digitization, and proper storage system.
Thesis
Keywords: Audiovisual Preservation, Conservation, Ghana Broadcasting Corporation, Accra, Ghana